Identification of medications that increase fall risk among residents in residential aged care facilities in Klang Valley, Malaysia - Arif Zikri Mazlan; Marhanis Omar; Adliah Mhd-Ali; Mohd Makmor-Bakry (Penerbit Universiti Kebangsaan Malaysia, 2021)
Frailty in the elderly is considered a contributor to falls and is increasingly recognized as a public health priority. Certain type of drugs is associated with the risk of falling. This study aimed to identify the use of drugs that may cause falls (FRIDs) among frail elderly residents in residential aged care facilities (RACF). A cross-sectional study was conducted among RACF residents in Klang Valley, Malaysia, who are 65 years old and above from December 2019 to March 2020 using a set of researcher-assisted and validated questionnaires upon their consent. A total of 72 elderly residents were included in this study. More than 90% of the residents were classified as the frail or pre-frail. The majority of them were taking fall-risk increasing drugs (n=53, 73.6%). The calcium channel blocker is the most common drug identified that may cause falls among the participants. No significant association was found between demographic data, frailty status, and fall risk with FRIDs usage in this study. The majority of the elderly residents were using drugs that may cause falls. Therefore, a periodical medication review is needed to prevent any potential harms towards the residents.